Multiple breakpoint test on crude oil price - Seuk Wai Phoong; Seuk Yen Phoong; Sedigheh Moghavvemi; Kok Hau Phoong (Foundations of Management, 2019)
The impact of structural changes as well as breaks on oil price fluctuations is studied in this article. There are a few channels, such as domestic prices and inflation, that cause the effect of oil price to pass through the economy. The higher crude oil price is immediately followed by the increase in oil products such as gasoline and heating oil. The direct effects continue as people choose alternative energy sources, leading to the increase in price. Besides, the indirect effect on inflation as a result of the behavioral responses of the firms and workers which is known as the "second round" effects in which higher wages is being demanded. This article uses exploratory data analysis to discover the patterns of the variables' series and then examines the relationship between oil price and consumer price index. Multiple breakpoint test is thereafter used to identify the structural changes in time-varying variables.
Keywords: C58; E32; 650; breakpoint test; consumer price index; oil price; exploratory data analysis